2014
DOI: 10.1007/s00253-014-5952-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of type II thioesterases and their application for secondary metabolite yield improvement

Abstract: A large number of antibiotics and other industrially important microbial secondary metabolites are synthesized by polyketide synthases (PKSs) and nonribosomal peptide synthetases (NRPSs). These multienzymatic complexes provide an enormous flexibility in formation of diverse chemical structures from simple substrates, such as carboxylic acids and amino acids. Modular PKSs and NRPSs, often referred to as megasynthases, have brought about a special interest due to the colinearity between enzymatic domains in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 64 publications
4
89
0
Order By: Relevance
“…23 TEIIs have a corrective (editing or proofreading) role, removing undesirable substrates and aberrantly loaded intermediates that would otherwise stall the NRPS/PKS biosynthetic pathway. 3033 In addition to an editing role, TEIIs have also been shown to participate in the selection of starter units incorporated into a pathway, 3436 release intermediates or final products, 37,38 regulate the yield of products, 39 and influence the overall performance of the synthases or synthetases. 30,34 Two models have been reported to account for the activity of TEIIs, a high specificity model where TEIIs hydrolyze only aberrant units and a low specificity model where the hydrolases act on both “correct” and “incorrect” intermediates with the “correct” released at a slower rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 TEIIs have a corrective (editing or proofreading) role, removing undesirable substrates and aberrantly loaded intermediates that would otherwise stall the NRPS/PKS biosynthetic pathway. 3033 In addition to an editing role, TEIIs have also been shown to participate in the selection of starter units incorporated into a pathway, 3436 release intermediates or final products, 37,38 regulate the yield of products, 39 and influence the overall performance of the synthases or synthetases. 30,34 Two models have been reported to account for the activity of TEIIs, a high specificity model where TEIIs hydrolyze only aberrant units and a low specificity model where the hydrolases act on both “correct” and “incorrect” intermediates with the “correct” released at a slower rate.…”
mentioning
confidence: 99%
“…40 Deletion of TEIIs in NRPS/PKS biosynthetic pathways commonly result in a decrease in the yield of the final natural product. 30,38,39,41 Although a large number of TEIIs have been identified, four TEIIs have been structurally characterized: RifR from the rifamycin hybrid NRPS/PKS pathway, 36 RedJ from the prodiginine hybrid NRPS/PKS, 39 SrfD from the surfactin NRPS, 42 and the human TEII involved in fatty acid synthesis. 43 Collectively these structures have revealed that unique structural conformations of TEIIs enable selective interactions with individual enzyme domains within the multidomain systems.…”
mentioning
confidence: 99%
“…21 Upon reexamination of the Leotiomycete-type echinocandin gene clusters responsible for echinocandins with 10,12-dimethylmyristoyl side chains, we speculated whether a putative hydrolase gene designated GLHYD (GLAREA_10032, EPE34338.1) downstream of the PKS might bear a TE domain. 22 Orthologues of GLHYD are absent in Aspergillus-type echinocandin gene clusters that encode for echinocandins with fatty-acid-derived acyl side chains, e.g., echinocandin B. 9 BLAST, PFAM, Protein Data Bank, and SWISS-MODEL similarity searches with the predicted amino acid sequence of GLHYD indicated that it belongs to the alpha/beta hydrolase protein family and contains a type II TE domain.…”
Section: Resultsmentioning
confidence: 99%
“…22,26,27 If this was the case, we might expect to observe a reduced level of pneumocandin production from fatty acid feeding experiments in a strain with a simultaneous double disruption of GLHYD and GLPKS compared to the ΔG LPKS4 strain. To test this hypothesis, pAg1-N3 (constructed in this study) was used to construct a disruption vector for GLHYD in Δ GLPKS4 .…”
Section: Resultsmentioning
confidence: 99%
“…HbaH encodes a type II thioesterase (TEII) [75] with similarity to BafH (67% protein sequence identity, 76% similarity). HbaJ encodes an AT homologue of the S. lohii gene product of orf2 (79% identity, 86% similarity).…”
Section: Resultsmentioning
confidence: 99%